Marketing Performance Model and Environment for Micro Business Scale Womenpreneurs Based on Competence in the Province of Riau - Putri, Librina Tria; ., Zulkarnain; Alwie, Alvi Furwanti; Wijayanto, Gatot (Journal of Ecohumanism, 2024)
This study aims to build a new conceptual model regarding the marketing performance of womenpreneurs, especially the micro-enterprise scale in Riau province, based on competence which is influenced by the ability of innovation, digital marketing, knowledge transfer, and networking. This study can fill the limitations of previous studies and gaps in research on women entrepreneurs in achieving marketing performance. This quantitative study collected data through questionnaires distributed to women entrepreneurs of micro-scale enterprises in Riau province. The sample calculation was carried out using the Krejcie-Morgan formula, resulting in 382 respondents using a stratified random sampling approach. The data collection technique used a questionnaire with a scale of 1-7, which was then processed using SmartPLS 3.0. This study examines the effect of innovation ability and digital marketing on competence and its impact on marketing performance with knowledge transfer and networking as moderators where this research has never been studied together.